The CoRoT Exoplanet program: status & results - Moutou C.; Deleuil M.; Bordé P. (EPJ Web of Conferences, 2011)
The CoRoT satellite is the ﬁrst instrument hunting for planets from space. We will review the status of the CoRoT/Exoplanet program. We will then present the CoRoT exoplanetary systems and how they widen the range of properties of the close-in population and contribute to our understanding of the properties of planets.